Nerve cuff electrode using embedded magnets and its application to hypoglossal nerve stimulation. (20th October 2016) - Seo, Jungmin; Wee, Jee Hye; Park, Jeong Hoan; Park, Pona; Kim, Jeong-Whun; Kim, Sung June
Abstract: Objective . A novel nerve cuff electrode with embedded magnets was fabricated and developed. In this study, a pair of magnets was fully embedded and encapsulated in a liquid crystal polymer (LCP) substrate to utilize magnetic force in order to replace the conventional installing techniques of cuff electrodes. In vitro and in vivo experiments were conducted to evaluate the feasibility of the magnet-embedded nerve cuff electrode (MENCE). Lastly, several issues pertaining to the MENCE such as the cuff-to-nerve diameter ratio, the force of the magnets, and possible concerns were discussed in the discussion section. Approach . Electrochemical impedance spectrum and cyclic voltammetry assessments were conducted to measure the impedance and charge storage capacity of the cathodal phase (CSCc ). The MENCE was installed onto the hypoglossal nerve (HN) of a rabbit and the movement of the genioglossus was recorded through C-arm fluoroscopy while the HN was stimulated by a pulsed current. Main results . The measured impedance was 0.638 ∠ −67.8° kΩ at 1 kHz and 5.27 ∠ −82.1° kΩ at 100 Hz. The average values of access resistance and cut-off frequency were 0.145 kΩ and 3.98 kHz, respectively. The CSCc of the electrode was measured as 1.69 mC cm −2 at the scan rate of 1 mV s −1 . The movement of the genioglossus contraction was observed under a pulsed current with an amplitude level of 0.106 mA, a rate of 0.635 kHz, and a duration of 0.375 ms applied through the MENCE. Significance. A few methods to close and secure cuff electrodes have been researched, but they are associated with several drawbacks. To overcome these, we used magnetic force as a closing method of the cuff electrode. The MENCE can be precisely installed on a target nerve without any surgical techniques such as suturing or molding. Furthermore, it is convenient to remove the installed MENCE because it requires little force to detach one magnet from the other, enabling repeatable installation and removal. We anticipate that the MENCE will become a very useful tool given its unique properties as a cuff electrode for neural engineering.